The ecological study of higher basidiomycetes as a supplement in the teaching of high school biology - Marquez, Modesto F. 1927- (1974)
The ecology of higher Basidiomycetes in Mercedes, Zamboanga City was observed in this study. It looked on the distribution of higher basidiomycetes in the area of the study, investigated the physical and biological factors affecting the growth of higher Basidiomycetes, stated the economic importance of the collected Basidiomycetes and utilized the ecological concepts demonstrated in the study for the enrichment of activities in high school biology.
Thesis (M.A.T. Biology)--University of the Philippines.
Keywords: idiomycetes; Biology -- Study and teaching (Secondary).; Fungi